Testosterone, personality traits and aggressive driving among young male drivers - Šucha, Matúš; Pillerová, M; Dominik, Tomáš; Vaculčíková Sedláčková, Zuzana; Domonkos, Emese; Hodosy, Július; Tóthová, Ľubomíra (Bratislavské lekárske listy, 2021)
INTRODUCTION: Psychological testing to examine potentially aggressive behaviour is a gold standard, but it is not sufficient. Testosterone might increase an aggressive behaviour. AIM: The aim of this study was to evaluate whether testosterone along with psychological assessment of fitness to drive could help to identify aggressive drivers. METHODS: Male participants (n=150) aged from 20 to 25, who possessed a driving license and drive at least 100 km per week, were evaluated in this study using an Inventory of traffic-relevant personality characteristics, the Sensation Seeking Scale and the Buss-Durkee Aggression Inventory. Saliva was collected for testosterone and cortisol measurements. The five binomial logistic models with dependent variables Caused an accident, Driving license taken away, Court trial, Intoxicated driving and Sporty self-report were tested in this study. RESULTS: The ‘Intoxicated driving’ model, was found to be statistically highly significant, explaining 48.8 % of the dependent variable’s variance (χ2(16)=36.145, p<0.01). In this model with sensation seeking, actual testosterone and their interaction was highly significant and explained 20.4 % of intoxicated driving variability (χ2(3)=14.283, p<0.01). This was higher than sensation seeking scores only. CONCLUSION: To conclude, salivary testosterone might prove a biological marker that improves the identification of those with a high probability of aggressive driving or its subtypes (Tab. 3, Ref. 53).
Keywords: agresivní jízda; Safety; Testosterone; Aggressive Driving; hydrokortison; lidé; testosteron; Adult; bezpečnost; Automobile Driving; Hydrocortisone; dospělí; Male; mladý dospělý; řízení motorových vozidel; Humans; mužské pohlaví; Young Adult